Existence and Concentrate Behavior of Schrödinger equations with critical exponential growth in R^N - Zhang, Jian; Zou, Wenming (Topological Methods in Nonlinear Analysis, 2016)
We consider the nonlinear Schrödinger equation equation* -Δ u + (1+μ g(x))u = f(u) in R^N, equation* where N 3, μ 0; the function g 0 has a potential well and f has critical growth. By using variational methods, the existence and concentration behavior of the ground state solution are obtained.